K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

15 tháng 9 2018

\(M=\left(2x+3\right)\left(2a-3\right)\left(4a^2+9\right)-\left(a^2+5\right)\left(a^2-5\right)\)

\(=\left(4a^2-9\right)\left(4a^2+9\right)-a^2+25\)

\(=16a^4-81-a^2+25\)

\(=16a^4-a^2-56\)

15 tháng 9 2018

M = ( 2a+3)(2x-3)(4a2+9) - (a2 + 5)(a2 - 5)

M =[ (2a)2 - 32 ][(2a2)+ 32 ] - [(a2)2 - 52 ]

M = (4a2)2 - (32)2 - a4 + 25

M = 16a4 - 81 - a4 +25

M = 15a4 - 56

24 tháng 7 2018

c,4x2-20x+25-4x2-20x-25+40x-1

=-1

AH
Akai Haruma
Giáo viên
15 tháng 9 2024

Lời giải:

$\frac{a^3+2a^2-1}{a^3-2a^2-2a+1}$

$=\frac{(a^3+a^2)+(a^2-1)}{(a^3+a^2)-(3a^2+3a)+(a+1)}$
$=\frac{a^2(a+1)+(a+1)(a-1)}{a^2(a+1)-3a(a+1)+(a+1)}$
$=\frac{(a+1)(a^2+a-1)}{(a+1)(a^2-3a+1)}$

$=\frac{a^2+a-1}{a^2-3a+1}$

21 tháng 8 2016

a/ \(16a^4+48a^3+4a^2-120a-72\)

b.\(2b^2+2a^2=4a\)

24 tháng 8 2016

a/ 36

b/ 2a+ 2 b2

\(7a\left(3a-5\right)+\left(2a-3\right)\left(4a+1\right)-\left(6a-2\right)^2\)

\(=21a^2-35a+8a^2+2a-12a-3-36a^2+24a-4\)

\(=-7a^2+4a-7\)